Development of a Flexible Piezoelectric Biosensor That Integrates BaTiO3–Poly(Dimethylsiloxane) for Posture Correction Applications - Menduh Furkan Aslan; Cem Özbek; Gökhan Yiğit; Mehmet Tosun; Seda Demirel Topel (Engineering Proceedings)
The prolonged issue of poor posture due to desk work has led to innovative technological remedies. This study shows the development of a flexible piezoelectric biosensor integrating BaTiO3 nanoparticles within a Polydimethylsiloxane (PDMS) matrix for practical posture correction. The biosensor is capable of real-time posture monitoring and correction by leveraging the piezoelectric properties of BaTiO3. Comprehensive synthesis and characterization using X-ray diffraction analysis (XRD) and transmission electron microscopy (TEM) validated the ideal particle size and crystalline structure of the composite. COMSOL Multiphysics simulations showed a peak potential of 0.87 volts under mechanical stress, which further confirmed the sensor’s efficiency. Electrical testing revealed that the sensor with 35 wt.% BaTiO3 exhibited a higher output voltage of 0.87 V compared to 0.34 V for the sensor with 30 wt.% BaTiO3, emphasizing its exceptional potential for addressing posture-related issues.